Studies of Blood Pressure and Prevalence of Hypertension in Schoolchildren in Jakarta - I. G. N. Wila Wirya; Husein Alatan; Taralan Tambunan; S. Harmanses; Endang Windiastuti (Paediatrica Indonesiana, 1988)
Blood pressure measurement was done on 4983 school children of 6 - 18 years schoolchildren was at random so that the sample population represented the children in Jakarta. The incidence of hypertension in this study is about 3.11 %, of which most are found at the age of 15 years.